Respuesta :

Answer:

Option ⇒ [tex]\frac{\sqrt[3]{5s^2t} }{st} \\[/tex]

Step-by-step explanation:

Given that ⇒ [tex]\frac{\sqrt[3]{5} }{\sqrt[3]{st^2} }[/tex]

To rationalizing the denominator, we need to make a perfect cube under cube root of the denominator

∴ By multiplying the denominator and numerator by ∛(s²t)

∴  [tex]\frac{\sqrt[3]{5} }{\sqrt[3]{st^2} }*\frac{\sqrt[3]{s^2t} }{\sqrt[3]{s^2t} } =\frac{\sqrt[3]{5s^2t} }{\sqrt[3]{s^3t^3} } = \frac{\sqrt[3]{5s^2t} }{st} \\[/tex]

The answer is the first option